The existence and singularity of the solution to the special integrative equation of Volterra - Akram Mahmood; Raed Qariakos (College of Education for Pure Sciences, 2006)
In this paper ,we investigate the existence and uniquence solution for homogeneous volterra integral equation of the second kind by using the method which is given by athinson ,A.F. These investigation lead us to the extending of some results of manafov ,M.D.